Counter-Discourse on The Criticism of Ibn Rushd Toward al-Ghazali - Ahmad Hakim (Jurnal Theologia, 2021)
Al-Ghazali's intellectuality and capabilities have been recognized worldwide until he was nicknamed H{ujjatul Islam. Therefore, if there are people who refute his thinking in many ways, then the refutation needs to be investigated further. In this case, Ibn Rushd rejected and blamed al-Ghazali's criticism of the peculiarities of the philosophers on three things, namely the nature’s immortality, God's knowledge, and physical resurrection. This study aims to find a clear position regarding the controversial discussion between Ibn Rushd and al-Ghazali. Both had different views on these three issues. This qualitative discussion with a critical hermeneutic approach presents various analyzes of the arguments of the two figures, especially concerning Ibn Rushd's criticism toward al-Ghazali. This study resulted in a conclusion that Ibn Rushd's criticism toward al-Ghazali can be said to still have gaps in his argumentation. When Ibn Rushd presented a proposition in the form of verses of the Qur'an, the verse he delivered supported al-Ghazali's opinion if analyzed in more depth, and was cross-checked with other verses.